Preparation method of energy-saving refractory material for RH refining furnace

By using a variety of raw materials with specific ratios, the problems of short service life and high maintenance costs of existing refractories are solved, and the thermal shock resistance, thermal conductivity and mechanical strength are achieved, which extends the service life and reduces energy consumption.

CN119591390APending Publication Date: 2025-03-11JIANGSU NUOMING HIGH TEMPERATURE MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411766429.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing refractory materials have a short service life in RH refining furnaces, high maintenance costs, and the risk of energy consumption and production interruption caused by frequent replacement is also high.

Method used

A refractory material composed of corundum, zirconia, high-purity magnesium sand, silicon carbide, ZrB2 powder, spinel powder, nanotitanium dioxide, graphene and carbon fiber is prepared through pretreatment, ball mill mixing, vibration molding and sintering treatment.

Benefits of technology

It improves the thermal shock resistance, thermal conductivity and mechanical strength of refractory materials, extends the service life, and reduces the risk of energy consumption and production interruption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591390A_ABST
    Figure CN119591390A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of refractory material preparation, in particular to a preparation method of an energy-saving refractory material for an RH refining furnace, and the preparation method comprises the following steps: S1, raw material pretreatment, S2, ball-milling mixing, S3, vibration molding, and S4, sintering treatment. The high-purity magnesia, corundum, zirconium oxide, Y2O3, silicon carbide and carbon fibers are pretreated, impurities are removed, the crystallinity is improved, and the crystal structure is stabilized; the two-way vibration molding treatment can enable the mixture to be more tightly arranged in the mold, so that the compactness of a green body is improved, and the heat insulation performance and the energy-saving effect of the refractory material are improved; according to the method, firstly slow heating and heat preservation are controlled, so that organic matters, impurities and the like in the green body can gradually react or be discharged, meanwhile, thermal stress caused by too fast heating is avoided, and the refractory material can adapt to complex high-temperature, strong-corrosion and other working environments of the RH refining furnace through the raw material combination in the method, so that the service life of the refractory material in the RH refining furnace is prolonged, and energy consumption is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory material preparation, and in particular to a method for preparing an energy-saving refractory material for an RH refining furnace. Background Art

[0002] RH refining furnace, also known as RH vacuum degassing furnace, is a key equipment used to improve the quality of molten steel in modern steel production. By circulating molten steel under vacuum conditions to remove harmful gases and non-metallic inclusions in steel, refining operations such as decarburization, alloying and temperature adjustment are carried out at the same time. The working principle of RH refining furnace is to use a vacuum pump to reduce the pressure in the furnace, transport molten steel from the steelmaking furnace to the RH refining furnace through a lift pipe, and then through argon stirring and vacuum treatment, finally the purified molten steel is returned to the steelmaking furnace or directly poured into the continuous casting machine.

[0003] Refractory materials play a vital role in RH refining furnaces. They must not only withstand extreme temperature changes and chemical erosion, but also have good thermal stability, thermal shock resistance and mechanical strength. The performance of refractory materials directly affects the service life, maintenance cost and refining quality of molten steel of RH refining furnaces. Therefore, the development of high-performance refractory materials is of great significance to improving the overall performance and energy saving effect of RH refining furnaces.

[0004] Energy-saving refractories are those that can improve thermal efficiency, reduce heat loss and extend service life. Due to the short service life and high maintenance cost of existing refractories, frequent replacement of refractories also brings high energy consumption and production interruption risks. In RH refining furnaces, unnecessary losses are often reduced by using refractories with higher high temperature resistance and pressure loss resistance, thereby reducing energy consumption. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a method for preparing an energy-saving refractory material for a RH refining furnace.

[0006] The technical solution of the present invention is: a method for preparing an energy-saving refractory material for an RH refining furnace, comprising the following steps: S1, raw material pretreatment

[0007] S1-1, by mass percentage, take 30-45% of corundum, 25-35% of zirconium oxide, 5-10% of silicon carbide, 3-6% of spinel powder, 3-5% of ZrB2 powder, 1-3% of Y2O3, 1-3% of carbon fiber, 0.5-1.5% of nano-titanium dioxide, 0.1-0.5% of graphene and the balance of high-purity magnesia;

[0008] The MgO content in the high-purity magnesia is 97-99wt%; the particle size of the spinel powder is 0.05-0.3mm, the particle size of the ZrB2 powder is 0.05-0.2mm, the length of the carbon fiber is 1-5mm, and the sheet diameter of the graphene is 1-10μm;

[0009] S1-2, pre-treating the high-purity magnesia, corundum, zirconium oxide, Y2O3, silicon carbide and carbon fiber to obtain high-purity magnesia powder, corundum fine powder, pre-sintered mixed powder of zirconium oxide and Y2O3, silicon carbide powder and copper-plated carbon fiber;

[0010] S2, ball milling

[0011] The high-purity magnesia powder, corundum fine powder, pre-sintered mixed powder of zirconium oxide and Y2O3, silicon carbide powder, ZrB2 powder, graphene, spinel powder, nano-titanium dioxide and copper-plated carbon fiber obtained in S1-2 are put into a ball mill according to the formula ratio and stirred evenly to obtain raw material powder; then 5-8% of the binder and 6-12% of water accounting for the total mass of the raw material powder are added in sequence, and the mixture is evenly mixed by ball milling to obtain a mixture;

[0012] S3, vibration molding

[0013] The mixed material described in S2 is introduced into a mold and subjected to a bidirectional vibration molding treatment for 15 to 25 minutes to obtain a green body;

[0014] S4. Sintering treatment

[0015] S4-1, placing the green body described in S3 in a drying oven and drying for 38 to 60 hours at a drying temperature of 100 to 150° C., reducing the moisture content of the green body to 0 to 0.5%, and obtaining a dry green body;

[0016] S4-2. Place the dry blocks described in S4-1 into a high-temperature furnace, heat them to 600-800°C at a rate of 3-8°C / min in a protective atmosphere of a mixture of hydrogen and argon, keep them warm for 3-4 hours, then heat them to 1500-1700°C at a rate of 2-5°C / min, keep them warm for 6-10 hours, and obtain a refractory material after taking them out of the furnace; the volume ratio of hydrogen to argon is 1:5-9.

[0017] Description: By controlling the amount of Y2O3 added, the crystal form of zirconium oxide is stabilized and the thermal shock resistance of the material is improved; adding a small amount of silicon carbide to the refractory material can improve the thermal conductivity of the material, help heat transfer, reduce local overheating, and improve the strength of the refractory material; nano titanium dioxide has high chemical and thermal stability, and can fill the tiny pores in the refractory material at high temperature to improve the density of the material. At the same time, its nano effect can enhance the material's antioxidant properties; ZrB2 in the refractory material can improve the material's high temperature strength and thermal shock resistance, and due to its conductivity, it can To improve the electromagnetic properties of refractory materials in the refining furnace, which is beneficial to the uniform distribution of heat; carbon fiber has high strength, high modulus and good thermal conductivity, and can form a thermal conductive network inside the refractory material, improve the uniformity of thermal conduction of the material, and enhance the overall mechanical strength of the refractory material; graphene has excellent thermal conductivity and mechanical properties, and can further improve the overall uniformity of thermal conduction of the material in the refractory material, and can also enhance the toughness of the material and improve the thermal shock resistance of the material; spinel powder has good corrosion resistance and thermal stability, which can increase the service life of the refractory material in the harsh environment of the refining furnace.

[0018] Further, the pretreatment method in S1-2 is: calcining the high-purity magnesia at a temperature of 1000-1200°C for 2-3h, and then crushing and screening to obtain high-purity magnesia powder with a particle size of 0.1-1mm; washing the corundum with water and drying it, and then sintering it at a temperature of 1600-1800°C for 1-2h, and then grinding it to obtain corundum fine powder with a particle size of 0.05-0.5mm; mixing the zirconium oxide with Y2O3, and then pre-sintering it at 1500-1600°C for 3-4h to obtain a pre-fired mixture, crushing and screening the pre-fired mixture to obtain a pre-fired mixed powder of zirconium oxide and Y2O3 with a particle size of 0.05-0.3mm; ball milling silicon carbide for 12-24h to obtain silicon carbide powder with a particle size of 0.01-0.1mm; copper plating the carbon fiber to obtain copper-plated carbon fiber.

[0019] Description: Calcination, crushing and screening of high-purity magnesia at a specific temperature can effectively remove moisture and volatile impurities and obtain magnesia powder of suitable particle size, thereby improving its purity and the uniformity of subsequent mixing; after washing, drying, high-temperature sintering and grinding, the surface impurities of corundum can be removed and fine powder of suitable particle size can be obtained, which is helpful to improve its refractory performance and its fusion with other raw materials; Zirconia and Y2O3 are mixed and pre-sintered, crushed and screened to obtain pre-burned mixed powder of zirconium oxide and Y2O3, which can optimize its structure and particle size and is conducive to improving the overall performance; Carbon fiber copper plating treatment to obtain copper-plated carbon fiber can help carbon fiber resist oxidation and corrosion, help enhance its thermal conductivity uniformity in refractory materials, increase the bonding force between carbon fibers, and the ductility of copper improves the comprehensive performance of refractory materials. When refractory materials experience thermal expansion and contraction or are subjected to local stress concentration, copper-plated carbon fiber can make refractory materials less likely to crack or break, thereby improving the toughness of refractory materials and making them more suitable for the complex environment of RH refining furnaces.

[0020] Furthermore, the copper plating treatment method of the carbon fiber is as follows: the carbon fiber is soaked and cleaned with an organic solvent for 1 to 2 hours, rinsed with deionized water and then dried, and then the cleaned carbon fiber is subjected to radio frequency plasma treatment for 15 to 30 minutes, and then the temperature is controlled to 20 to 30°C, and the carbon fiber treated with plasma is placed in an acidic solution and soaked for 2 to 6 minutes to obtain a roughened carbon fiber; the roughened carbon fiber is placed in a stannous chloride solution with a concentration of 10 to 20 g / L and soaked for 10 to 20 minutes, and after being taken out, it is placed in a silver nitrate solution with a concentration of 1 to 3 g / L and soaked for 5 to 15 minutes to obtain an activated carbon fiber; the temperature is controlled to 30 to 40°C, and the activated carbon fiber is placed in a copper plating solution for chemical copper plating for 30 to 60 minutes, so that a copper layer is deposited on the surface of the carbon fiber, and the thickness of the copper layer is controlled to be 0.1 to 0.3 μm, to obtain a copper-plated carbon fiber.

[0021] Description: Organic solvent immersion cleaning and deionized water rinsing and drying can effectively remove impurities on the carbon fiber surface and provide a clean surface for subsequent processing; radio frequency plasma treatment can change the physical and chemical properties of the carbon fiber surface, increase its surface activity, and facilitate the subsequent steps; soaking in an acidic solution at a specific temperature to obtain coarsened carbon fiber helps to enhance the effect of the carbon fiber with subsequent sensitizing solution and activation solution; soaking in stannous chloride solution and silver nitrate solution can further activate the carbon fiber surface, making the copper plating reaction easier and more uniform.

[0022] Furthermore, the acidic solution is a mixture of concentrated nitric acid and concentrated sulfuric acid, the volume ratio of the concentrated nitric acid to the concentrated sulfuric acid is 1:2-3, the mass concentration of the concentrated nitric acid is 68-72%, and the mass concentration of the concentrated sulfuric acid is 95-98%.

[0023] Description: Concentrated sulfuric acid has strong oxidizing and dehydrating properties, and concentrated nitric acid also has strong oxidizing properties. The oxidizing properties are further enhanced after the two are mixed. In the surface treatment process, impurities, oxides, etc. can be removed more thoroughly, and the appropriate ratio range helps to accurately control the intensity and reaction rate of the reaction, while also ensuring the safety and operability of the reaction process to a certain extent.

[0024] Furthermore, the working gas for the radio frequency plasma treatment is argon and oxygen in a volume ratio of 4 to 5:1, the gas pressure is 5 to 10 Pa, and the power is set to 100 to 200W.

[0025] Description: Argon is stable in nature and can prevent adverse effects such as excessive oxidation of carbon fiber during the treatment process, while playing a certain role in protecting and maintaining the stability of the plasma environment; the presence of oxygen helps to oxidize the surface of carbon fiber and improve its surface chemical activity. The appropriate volume ratio ensures that argon and oxygen work together and accurately control the state of plasma, so that the surface of carbon fiber is properly treated, which can effectively improve the surface activity for better subsequent copper plating and other operations, and will not cause structural damage or performance degradation to the carbon fiber due to excessive energy or gas ratio imbalance.

[0026] Furthermore, the copper plating solution contains: 15-26 g / L of disodium ethylenediaminetetraacetate, 10-22 g / L of copper sulfate, 10-18 g / L of nitrilotriacetic acid, 10-15 ml / L of formaldehyde, 8-12 g / L of potassium hydroxide, and the solvent is water.

[0027] Description: Disodium ethylenediaminetetraacetic acid can play a complexing role, which helps to stabilize the metal ions in the solution, such as the copper ions in copper sulfate, so that the copper plating process can proceed steadily; copper sulfate is the source of copper ions, providing the necessary material basis for copper plating on the surface of carbon fiber; nitrilotriacetic acid also participates in the complexing reaction, assisting in adjusting the chemical properties of the solution; formaldehyde, as a reducing agent, can reduce copper ions to copper elements and deposit them on the surface of carbon fiber to achieve copper plating; potassium hydroxide can adjust the pH of the solution to ensure that the solution is in a pH environment suitable for the copper plating reaction.

[0028] Furthermore, the ball milling mixing time in S2 is 18 to 30 hours, the rotation speed is 120 to 180 rpm, and the binder is phenolic resin.

[0029] Note: The ball milling mixing time of 18 to 30 hours and the rotation speed of 120 to 180 rpm can make the materials fully mixed and uniform, ensuring that the various components have enough time and energy to interact with each other in this time period and rotation speed, avoiding the influence of local uneven components on the overall performance of the product; phenolic resin as a binder has good adhesion, it can effectively bond other materials together, enhance the stability of the system, help maintain the integrity of the structure during subsequent processing or use, thereby improving the quality and performance of the final product.

[0030] Furthermore, the vibration frequency in S3 is 30-55 Hz, the molding pressure is 130-185 MPa, and the holding time is 1-2 h.

[0031] Description: The vibration frequency of 30-55Hz can make the materials better arranged and filled during the molding process, reduce internal voids, and improve the density after molding; the molding pressure of 130-185MPa provides sufficient external force for material molding, promotes the close combination of materials, and ensures that the product has good shape and mechanical properties; the holding time of 1-2h can keep the product stable under pressure, further consolidate its structure, and prevent deformation or loose internal structure after pressure release, thereby improving the quality and stability of the final product.

[0032] The beneficial effects of the present invention are:

[0033] (1) The present invention selects basic raw materials such as corundum, zirconium oxide, and high-purity magnesia sand to have good refractory properties within different temperature ranges; the high hardness and high melting point of corundum, the high temperature resistance and thermal shock resistance of zirconium oxide, and the alkaline refractory properties of high-purity magnesia sand enhance the comprehensive properties of the material; the high thermal conductivity and oxidation resistance of silicon carbide, the high melting point and oxidation resistance of ZrB2 powder, and spinel powder help to improve the structural stability of the material; nano-titanium dioxide and graphene can refine the grains, improve the density of the material, and improve the uniformity of the thermal conductivity of the material. The raw material combination of the present method enables the refractory material to adapt to the complex high temperature, strong corrosion and other working environments of the RH refining furnace, thereby improving the service life of the refractory material and avoiding the energy consumption and production interruption risks caused by frequent replacement of refractory materials.

[0034] (2) The present invention can remove impurities, improve crystallinity and stabilize crystal structure by pretreating high-purity magnesia, corundum, zirconium oxide, Y2O3, silicon carbide and carbon fiber; the bidirectional vibration molding process can make the mixture more densely arranged in the mold, discharge the internal air, and improve the density of the green body, thereby reducing gas penetration and heat loss through gas convection, improving the thermal insulation performance and energy-saving effect of the refractory material, and ensuring the uniformity of green body quality; controlling the slow heating and heat preservation first can make the organic matter, impurities and the like in the green body react or be discharged gradually, while avoiding thermal stress caused by too fast heating; sintering under a protective atmosphere can prevent the components in the green body from being oxidized, which is helpful to form a refractory material with dense structure and stable performance, reduce internal defects of the material, improve the oxidation resistance and high temperature performance of the refractory material, thereby extending its service life in the RH refining furnace and reducing energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 is a bar graph of compressive strength test of samples of Examples 1 to 13, 18 to 21 of the present invention and Comparative Examples 1 to 6;

[0036] Figure 2 It is a bar graph of the line change rate test after burning of samples of Examples 1 to 13, 18 to 21 of the present invention and Comparative Examples 1 to 6. DETAILED DESCRIPTION

[0037] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0038] Embodiment 1:

[0039] A method for preparing an energy-saving refractory material for an RH refining furnace comprises the following steps:

[0040] S1. Raw material pretreatment

[0041] S1-1, by mass percentage, take 37.5% of corundum, 30% of zirconium oxide, 7.5% of silicon carbide, 4.5% of spinel powder, 4% of ZrB2 powder, 2% of Y2O3, 2% of carbon fiber, 1% of nano-titanium dioxide, 0.3% of graphene and the balance of high-purity magnesia;

[0042] The MgO content in the high-purity magnesia is 98wt%; the particle size of the spinel powder is 0.2-0.25mm, the particle size of the ZrB2 powder is 0.1-0.15mm, the length of the carbon fiber is 2.5-3mm, and the sheet diameter of the graphene is 5-6μm;

[0043] S1-2, calcining the high-purity magnesia at 1100°C for 2.5h, and then crushing and screening to obtain high-purity magnesia powder with a particle size of 0.5-0.7mm; washing the corundum with water and drying it, sintering it at 1700°C for 1.5h, and then grinding it to obtain corundum fine powder with a particle size of 0.2-0.3mm; mixing the zirconium oxide with Y2O3, and then pre-sintering it at 1550°C for 3.5h to obtain a pre-sintered mixture, crushing and screening the pre-sintered mixture to obtain a pre-sintered mixed powder of zirconium oxide and Y2O3 with a particle size of 0.1-0.2mm; ball-milling the silicon carbide for 18h to obtain silicon carbide powder with a particle size of 0.05-0.08mm;

[0044] The carbon fiber was soaked and cleaned in an acetone solution with a mass concentration of 95% for 1.5 hours, rinsed with deionized water and dried, and then the cleaned carbon fiber was subjected to radio frequency plasma treatment for 22.5 minutes, and then the temperature was controlled to 25°C, and the carbon fiber treated with plasma was placed in an acidic solution and soaked for 4 minutes to obtain a roughened carbon fiber; the roughened carbon fiber was placed in a stannous chloride aqueous solution with a concentration of 15g / L and soaked for 15 minutes, and then taken out and placed in a silver nitrate aqueous solution with a concentration of 2g / L and soaked for 10 minutes to obtain an activated carbon fiber; the temperature was controlled to 35°C, and the activated carbon fiber was placed in a copper plating solution for chemical copper plating for 45 minutes, so that a copper layer was deposited on the surface of the carbon fiber, and the thickness of the copper layer was controlled to be 0.2-0.25μm, to obtain a copper-plated carbon fiber;

[0045] The acidic solution is a mixed solution of concentrated nitric acid and concentrated sulfuric acid, the volume ratio of the concentrated nitric acid to the concentrated sulfuric acid is 1:2.5, the mass concentration of the concentrated nitric acid is 70%, and the mass concentration of the concentrated sulfuric acid is 96.5%;

[0046] The working gas for the RF plasma treatment is argon and oxygen with a volume ratio of 4.5:1, the gas pressure is 7.5 Pa, and the power is set to 150 W;

[0047] The copper plating solution contains: 20 g / L of disodium ethylenediaminetetraacetate, 16 g / L of copper sulfate, 14 g / L of nitrilotriacetic acid, 12.5 ml / L of formaldehyde, and 10 g / L of potassium hydroxide, and the solvent is water;

[0048] S2, ball milling

[0049] The high-purity magnesia powder, corundum fine powder, pre-sintered mixed powder of zirconium oxide and Y2O3, silicon carbide powder, ZrB2 powder, graphene, spinel powder, nano-titanium dioxide and copper-plated carbon fiber obtained in S1-2 are put into a ball mill according to the formula ratio and stirred evenly to obtain raw material powder; then 6.5% of the total mass of the raw material powder and 9% of water are added in sequence, and the mixture is evenly mixed by ball milling to obtain a mixture; the ball milling mixing time in S2 is 24h, the rotation speed is 150rpm, and the binder is phenolic resin;

[0050] S3, vibration molding

[0051] The mixed material described in S2 is introduced into the mold and subjected to bidirectional vibration molding treatment for 20 minutes, the vibration frequency is 42 Hz, the molding pressure is 153 MPa, and the holding time is 1.5 hours to obtain a green body;

[0052] S4. Sintering treatment

[0053] S4-1, placing the green body described in S3 in a drying oven and drying for 49 hours at a drying temperature of 125° C., reducing the moisture content of the green body to 0.25%, thereby obtaining a dry green body;

[0054] S4-2. Put the dry blocks described in S4-1 into a high-temperature furnace, heat them to 700°C at a rate of 5.5°C / min in a protective atmosphere of a mixture of hydrogen and argon, keep them warm for 3.5 hours, then heat them to 1600°C at a rate of 3.5°C / min, keep them warm for 8 hours, and obtain a refractory material after taking it out of the furnace; the volume ratio of hydrogen to argon is 1:7.

[0055] Example 2: This example is basically the same as Example 1, except that, by mass percentage, 30% of corundum, 25% of zirconium oxide, 5% of silicon carbide, 3% of spinel powder, 3% of ZrB2 powder, 1% of Y2O3, 1% of carbon fiber, 0.5% of nano-titanium dioxide, 0.1% of graphene and the remainder of high-purity magnesia are taken.

[0056] Example 3: This example is basically the same as Example 1, except that, by mass percentage, 45% of corundum, 35% of zirconium oxide, 10% of silicon carbide, 6% of spinel powder, 5% of ZrB2 powder, 3% of Y2O3, 3% of carbon fiber, 1.5% of nano-titanium dioxide, 0.5% of graphene and the remainder of high-purity magnesia are taken.

[0057] Example 4: This example is basically the same as Example 1, except that the MgO content in the high-purity magnesia is 97wt%; the particle size of the spinel powder is 0.05-0.1mm, the particle size of the ZrB2 powder is 0.05-0.1mm, the length of the carbon fiber is 1-2mm, and the flake diameter of the graphene is 1-2μm.

[0058] Example 5: This example is basically the same as Example 1, except that the MgO content in the high-purity magnesia is 99wt%; the particle size of the spinel powder is 0.2-0.3mm, the particle size of the ZrB2 powder is 0.1-0.2mm, the length of the carbon fiber is 4-5mm, and the flake diameter of the graphene is 9-10μm.

[0059] Example 6: This example is basically the same as Example 1, except that the high-purity magnesia is calcined at 1000°C for 2 hours, and then crushed and sieved to obtain high-purity magnesia powder with a particle size of 0.1 to 0.3 mm; the corundum is washed with water and dried, and then sintered at 1600°C for 1 hour, and then ground to obtain corundum fine powder with a particle size of 0.05 to 0.1 mm; the zirconium oxide is mixed with Y2O3, and then pre-sintered at 1500°C for 3 hours to obtain a pre-fired mixture, and the pre-fired mixture is crushed and sieved to obtain a pre-fired mixed powder of zirconium oxide and Y2O3 with a particle size of 0.05 to 0.1 mm; the silicon carbide is ball-milled for 12 hours to obtain silicon carbide powder with a particle size of 0.01 to 0.08 mm.

[0060] Example 7: This example is basically the same as Example 1, except that the high-purity magnesia is calcined at 1200°C for 3 hours, and then crushed and sieved to obtain high-purity magnesia powder with a particle size of 0.8-1 mm; the corundum is washed with water and dried, and then sintered at 1800°C for 2 hours, and then ground to obtain corundum fine powder with a particle size of 0.45-0.5 mm; the zirconium oxide is mixed with Y2O3, and then pre-sintered at 1600°C for 4 hours to obtain a pre-fired mixture, and the pre-fired mixture is crushed and sieved to obtain a pre-fired mixed powder of zirconium oxide and Y2O3 with a particle size of 0.25-0.3 mm; silicon carbide is ball-milled for 24 hours to obtain silicon carbide powder with a particle size of 0.08-0.1 mm.

[0061] Example 8: This example is basically the same as Example 1, except that the carbon fiber is soaked and cleaned with an acetone solution with a mass concentration of 95% for 1 hour, rinsed with deionized water and dried, and then the cleaned carbon fiber is subjected to radio frequency plasma treatment for 15 minutes, and then the temperature is controlled to 20°C, and the carbon fiber after plasma treatment is immersed in an acidic solution for 2 minutes to obtain roughened carbon fiber; the roughened carbon fiber is immersed in a stannous chloride aqueous solution with a concentration of 10g / L for 10 minutes, and then taken out and immersed in a silver nitrate aqueous solution with a concentration of 1g / L for 5 minutes to obtain activated carbon fiber; the temperature is controlled to 30°C, and the activated carbon fiber is immersed in a copper plating solution for chemical copper plating for 30 minutes, so that a copper layer is deposited on the surface of the carbon fiber, and the thickness of the copper layer is controlled to be 0.1-0.2μm to obtain copper-plated carbon fiber.

[0062] Example 9: This example is basically the same as Example 1, except that the carbon fiber is soaked and cleaned with an acetone solution with a mass concentration of 95% for 2 hours, rinsed with deionized water and dried, and then the cleaned carbon fiber is subjected to radio frequency plasma treatment for 30 minutes, and then the temperature is controlled to 30°C, and the carbon fiber after plasma treatment is immersed in an acidic solution for 6 minutes to obtain a roughened carbon fiber; the roughened carbon fiber is immersed in a stannous chloride aqueous solution with a concentration of 20g / L for 20 minutes, and then taken out and immersed in a silver nitrate aqueous solution with a concentration of 3g / L for 15 minutes to obtain an activated carbon fiber; the temperature is controlled to 40°C, and the activated carbon fiber is immersed in a copper plating solution for chemical copper plating for 60 minutes, so that a copper layer is deposited on the surface of the carbon fiber, and the thickness of the copper layer is controlled to be 0.2-0.3μm to obtain a copper-plated carbon fiber.

[0063] Example 10: This example is basically the same as Example 1, except that the working gas for the RF plasma treatment is argon and oxygen in a volume ratio of 4:1, the gas pressure is 5 Pa, and the power is set to 100 W.

[0064] Example 11: This example is basically the same as Example 1, except that the working gas for the RF plasma treatment is argon and oxygen in a volume ratio of 5:1, the gas pressure is 10Pa, and the power is set to 200W.

[0065] Example 12: This example is basically the same as Example 1, except that the copper plating solution contains: 15g / L disodium ethylenediaminetetraacetic acid, 10g / L copper sulfate, 10g / L nitrilotriacetic acid, 10ml / L formaldehyde, 8g / L potassium hydroxide, and the solvent is water.

[0066] Example 13: This example is basically the same as Example 1, except that the copper plating solution contains: 26 g / L of disodium ethylenediaminetetraacetic acid, 22 g / L of copper sulfate, 18 g / L of nitrilotriacetic acid, 15 ml / L of formaldehyde, 12 g / L of potassium hydroxide, and the solvent is water.

[0067] Example 14: This example is basically the same as Example 1, except that 5% of a binder and 6% of water accounting for the total mass of the raw material powder are added in sequence, and the mixture is evenly mixed by ball milling to obtain a mixture; the ball milling mixing time in S2 is 18h, the rotation speed is 120rpm, and the binder is phenolic resin.

[0068] Example 15: This example is basically the same as Example 1, except that 8% of a binder and 12% of water accounting for the total mass of the raw material powder are added in sequence, and the mixture is evenly mixed by ball milling to obtain a mixture; the ball milling mixing time in S2 is 30h, the rotation speed is 180rpm, and the binder is phenolic resin.

[0069] Example 16: This example is basically the same as Example 1, except that the mixture described in S2 is introduced into the mold and subjected to bidirectional vibration molding treatment for 15 minutes, the vibration frequency is 30Hz, the molding pressure is 130MPa, and the holding time is 1h to obtain a green body.

[0070] Example 17: This example is basically the same as Example 1, except that the mixture described in S2 is introduced into the mold and subjected to bidirectional vibration molding treatment for 25 minutes, the vibration frequency is 55 Hz, the molding pressure is 185 MPa, and the holding time is 2 hours to obtain a green body.

[0071] Example 18: This example is basically the same as Example 1, except that the green body described in S3 is placed in a drying oven and dried for 38 hours at a drying temperature of 100°C, so that the moisture content in the green body is reduced to 0% to obtain a dry green body.

[0072] Example 19: This example is basically the same as Example 1, except that the green body described in S3 is placed in a drying oven and dried for 60 hours at a drying temperature of 150°C, so that the moisture content in the green body is reduced to 0.5% to obtain a dry green body.

[0073] Example 20: This example is basically the same as Example 1, except that the dry blank described in S4-1 is placed in a high-temperature furnace, heated to 600°C at a rate of 3°C / min in a protective atmosphere of a mixture of hydrogen and argon, kept warm for 3 hours, then heated to 1500°C at a rate of 2°C / min, kept warm for 6 hours, and a refractory material is obtained after taking out of the furnace; the volume ratio of hydrogen to argon is 1:5.

[0074] Example 21: This example is basically the same as Example 1, except that the dry blank described in S4-1 is placed in a high-temperature furnace, heated to 800°C at a rate of 8°C / min in a protective atmosphere of a mixture of hydrogen and argon, kept warm for 4 hours, then heated to 1700°C at a rate of 5°C / min, kept warm for 10 hours, and a refractory material is obtained after taking out of the furnace; the volume ratio of hydrogen to argon is 1:9.

[0075] Control Example 1: Taking Example 1 as a reference, take, by mass percentage, 25% of corundum, 20% of zirconium oxide, 4% of silicon carbide, 2% of spinel powder, 2% of ZrB2 powder, 0.5% of Y2O3, 0.5% of carbon fiber, 0.2% of nano-titanium dioxide, 0.05% of graphene and the remainder of high-purity magnesia.

[0076] Control Example 2: With reference to Example 1, the MgO content in the high-purity magnesia is 96wt% by mass; the particle size of the spinel powder is 0.02-0.03mm, the particle size of the ZrB2 powder is 0.01-0.03mm, the length of the carbon fiber is 0.5-0.8mm, and the flake diameter of the graphene is 0.3-0.8μm.

[0077] Comparative Example 3: With reference to Example 1, the high-purity magnesia is calcined at 900°C for 1.5h, and then crushed and sieved to obtain high-purity magnesia powder with a particle size of 0.05-0.1mm; the corundum is washed with water and dried, and then sintered at 1550°C for 0.8h, and then ground to obtain corundum fine powder with a particle size of 0.01-0.04mm; the zirconium oxide is mixed with Y2O3, and then pre-sintered at 1550°C for 2.5h to obtain a pre-burned mixture, and the pre-burned mixture is crushed and sieved to obtain a pre-burned mixed powder of zirconium oxide and Y2O3 with a particle size of 0.01-0.03mm; silicon carbide is ball-milled for 10h to obtain silicon carbide powder with a particle size of 0.005-0.009mm.

[0078] Comparative Example 4: In S1-2, the carbon fiber is not pre-treated and plated.

[0079] Comparative Example 5: Taking Example 1 as a reference, the carbon fiber was soaked and cleaned in an acetone solution with a mass concentration of 95% for 3 hours, rinsed with deionized water and dried, and then the cleaned carbon fiber was subjected to radio frequency plasma treatment for 35 minutes, and then the temperature was controlled to 35°C, and the carbon fiber after plasma treatment was immersed in an acidic solution for 7 minutes to obtain a roughened carbon fiber; the roughened carbon fiber was immersed in a stannous chloride aqueous solution with a concentration of 25g / L for 30 minutes, and after being taken out, it was immersed in a silver nitrate aqueous solution with a concentration of 4g / L for 20 minutes to obtain an activated carbon fiber; the temperature was controlled to 45°C, and the activated carbon fiber was placed in a copper plating solution for chemical copper plating for 65 minutes to deposit a copper layer on the surface of the carbon fiber, and the thickness of the copper layer was controlled to be 0.1-0.3μm to obtain a copper-plated carbon fiber.

[0080] Control Example 6: Taking Example 1 as a reference, the dry blank described in S4-1 is placed in a high-temperature furnace, and the temperature is increased to 900°C at a rate of 10°C / min in a protective atmosphere of a mixture of hydrogen and argon, and kept warm for 5 hours. Then, the temperature is increased to 1800°C at a rate of 6°C / min, and kept warm for 12 hours. After taking out of the furnace, a refractory material is obtained; the volume ratio of hydrogen to argon is 1:10.

[0081] In order to explore the refractory performance of some embodiments and control examples, the main materials were determined according to the experimental formula and samples were obtained for testing. They were dried at 110°C for 24 hours and kept at 1500°C for 3 hours. According to GB / T3001-2007 and GB / T5988-2007, the compressive strength and post-burning linear change rate of the refractory were tested respectively. The results are as follows: Figure 1 , 2 The specific research is as follows:

[0082] 1. Explore the influence of batching parameters on the performance of refractory materials:

[0083] like Figure 1 , 2 As shown, by comparing Examples 1 to 3, it can be seen that: Example 1 has the highest compressive strength and the smallest line change after burning, and its comprehensive performance is better; changing the raw material ratio parameters will have a certain impact on the prepared refractory material sample, and Example 2 has the lowest compressive strength; By comparing Example 1 with Examples 4 and 5, it can be seen that Example 4 has the best pressure resistance, but the line change after burning is slightly greater than that of Example 1. Changing the purity, particle size, length, and sheet diameter parameters of the raw materials will have a certain impact on the pressure resistance and refractory performance of the prepared samples;

[0084] By comparing with control examples 1 and 2, it can be seen that the pressure resistance and refractory performance of the samples prepared by using process parameters beyond the scope of this method are significantly reduced. The pressure resistance and refractory performance of control example 1 are lower than those of control example 2. The comprehensive performance of control example 1 is much lower than that of example 2. It can be seen that the refractory material prepared by using the process parameter values ​​of example 1 has the best comprehensive performance.

[0085] 2. Explore the influence of pretreatment process parameters on refractory performance:

[0086] like Figure 1 , 2 As shown, by comparing Examples 1, 6 and 7, it can be seen that: it can be seen that Example 1 has the best comprehensive performance; the compressive strength of Example 6 is better than that of Example 7, and the high temperature resistance of Example 7 is slightly higher than that of Example 6. Changing the process parameters of the pretreatment will have a certain effect on the performance of the refractory samples. The comprehensive performance of Control Example 3 is much lower than that of Examples 6 and 7. Among them, the refractory material prepared by the process parameter values ​​closer to Example 1 has the best comprehensive performance.

[0087] 3. Investigate the influence of process parameters of carbon fiber coating on the performance of refractory materials:

[0088] like Figure 1 , 2As shown, by comparing Examples 1, 8, and 9, it can be seen that the comprehensive performance of the refractory material prepared according to the method of Example 1 is the best, and the pressure resistance and refractory performance of Example 8 are better than those of Example 9. It can be seen that the process parameters of the modification treatment can have a certain influence on the performance of the refractory material, and controlling the appropriate ratio can improve its compressive strength and refractory performance;

[0089] By comparing Examples 1, 10, and 11, it can be seen that Example 1 has the best comprehensive performance, and the pressure resistance and fire resistance of the sample of Example 10 is slightly lower than that of Example 11. Changing the process parameters of the radio frequency plasma treatment can have a certain effect on the sample performance; by comparing Examples 1, 12, and 13, it can be seen that Example 1 has the best comprehensive performance, and the pressure resistance and fire resistance of the sample of Example 12 is slightly lower than that of Example 13. Changing the ratio parameters of the copper plating solution can have a certain effect on the sample performance, but the difference is not obvious.

[0090] From the comparison between Example 1 and Control Examples 4 and 5, it can be seen that the compressive strength and the post-firing linear change rate of Control Example 5 are significantly better than those of Control Example 4, but far lower than those of Example 1. The carbon fiber coating treatment operation and the change in its process parameter range have a more obvious effect on the effect of the refractory material. The refractory material prepared within the parameter range of this scheme has better comprehensive performance.

[0091] 4. Explore the influence of sintering process parameters on the performance of refractory materials:

[0092] Comparing Examples 1, 18, and 19, it can be seen that Example 1 has the best comprehensive performance and is similar to Example 19. The pressure resistance and fire resistance of the sample of Example 18 are slightly lower than those of Example 19. Changing the process parameters of the green body treatment can have a certain effect on the sample performance, but the difference is not obvious. Comparing Examples 1, 20, and 21, it can be seen that Example 1 has the best comprehensive performance, and the pressure resistance and fire resistance of the sample of Example 20 is lower than that of Example 21. Changing the process parameters of the sintering treatment can have a certain effect on the sample performance.

[0093] From the comparison between Example 1 and Control Example 6, it can be seen that the compressive strength and the post-firing linear change rate of Example 1 are significantly better than those of Control Example 6. The change in the process parameter range of the sintering treatment has a more obvious effect on the effect of the refractory material. The refractory material prepared by using the parameters within the parameter range of this scheme has better comprehensive performance.

Claims

1. A method for preparing an energy-saving refractory material for a RH refining furnace, characterized in that: The following steps are involved: S1. Raw material pretreatment S1-1, by mass percentage, take 30-45% of corundum, 25-35% of zirconium oxide, 5-10% of silicon carbide, 3-6% of spinel powder, 3-5% of ZrB2 powder, 1-3% of Y2O3, 1-3% of carbon fiber, 0.5-1.5% of nano-titanium dioxide, 0.1-0.5% of graphene and the balance of high-purity magnesia; The MgO content in the high-purity magnesia is 97-99wt%; the particle size of the spinel powder is 0.05-0.3mm, the particle size of the ZrB2 powder is 0.05-0.2mm, the length of the carbon fiber is 1-5mm, and the sheet diameter of the graphene is 1-10μm; S1-2, pre-treating the high-purity magnesia, corundum, zirconium oxide, Y2O3, silicon carbide and carbon fiber to obtain high-purity magnesia powder, corundum fine powder, pre-sintered mixed powder of zirconium oxide and Y2O3, silicon carbide powder and copper-plated carbon fiber; S2, ball milling The high-purity magnesia powder, corundum fine powder, pre-sintered mixed powder of zirconium oxide and Y2O3, silicon carbide powder, ZrB2 powder, graphene, spinel powder, nano-titanium dioxide and copper-plated carbon fiber obtained in S1-2 are put into a ball mill according to the formula ratio and stirred evenly to obtain raw material powder; then 5-8% of the binder and 6-12% of water accounting for the total mass of the raw material powder are added in sequence, and the mixture is evenly mixed by ball milling to obtain a mixture; S3, vibration molding The mixed material described in S2 is introduced into a mold and subjected to a bidirectional vibration molding treatment for 15 to 25 minutes to obtain a green body; S4. Sintering treatment S4-1, placing the green body described in S3 in a drying oven and drying for 38 to 60 hours at a drying temperature of 100 to 150° C., reducing the moisture content of the green body to 0 to 0.5%, and obtaining a dry green body; S4-2. Place the dry blocks described in S4-1 into a high-temperature furnace, heat them to 600-800°C at a rate of 3-8°C / min in a protective atmosphere of a mixture of hydrogen and argon, keep them warm for 3-4 hours, then heat them to 1500-1700°C at a rate of 2-5°C / min, keep them warm for 6-10 hours, and obtain a refractory material after taking them out of the furnace; the volume ratio of hydrogen to argon is 1:5-9.

2. The method for preparing an energy-saving refractory material for a RH refining furnace according to claim 1, characterized in that: The pretreatment method in S1-2 is: calcining the high-purity magnesia at a temperature of 1000-1200°C for 2-3h, and then crushing and screening to obtain high-purity magnesia powder with a particle size of 0.1-1mm; washing the corundum with water and drying it, and then sintering it at a temperature of 1600-1800°C for 1-2h, and then grinding it to obtain corundum fine powder with a particle size of 0.05-0.5mm; mixing the zirconium oxide with Y2O3, and then pre-sintering it at 1500-1600°C for 3-4h to obtain a pre-fired mixture, crushing and screening the pre-fired mixture to obtain a pre-fired mixed powder of zirconium oxide and Y2O3 with a particle size of 0.05-0.3mm; ball milling silicon carbide for 12-24h to obtain silicon carbide powder with a particle size of 0.01-0.1mm; copper plating the carbon fiber to obtain copper-plated carbon fiber.

3. The method for preparing an energy-saving refractory material for a RH refining furnace according to claim 2, characterized in that: The copper plating treatment method of the carbon fiber is as follows: the carbon fiber is soaked and cleaned with an organic solvent for 1 to 2 hours, rinsed with deionized water and then dried, and then the cleaned carbon fiber is subjected to radio frequency plasma treatment for 15 to 30 minutes, and then the temperature is controlled to 20 to 30° C., and the carbon fiber treated with plasma is placed in an acidic solution and soaked for 2 to 6 minutes to obtain a roughened carbon fiber; the roughened carbon fiber is placed in a stannous chloride aqueous solution with a concentration of 10 to 20 g / L and soaked for 10 to 20 minutes, and after being taken out, it is placed in a silver nitrate aqueous solution with a concentration of 1 to 3 g / L and soaked for 5 to 15 minutes to obtain an activated carbon fiber; the temperature is controlled to 30 to 40° C., and the activated carbon fiber is placed in a copper plating solution for chemical copper plating for 30 to 60 minutes, so that a copper layer is deposited on the surface of the carbon fiber, and the thickness of the copper layer is controlled to be 0.1 to 0.3 μm, so as to obtain a copper-plated carbon fiber.

4. The method for preparing an energy-saving refractory material for a RH refining furnace according to claim 3, characterized in that: The acidic solution is a mixed solution of concentrated nitric acid and concentrated sulfuric acid, the volume ratio of the concentrated nitric acid to the concentrated sulfuric acid is 1:2-3, the mass concentration of the concentrated nitric acid is 68-72%, and the mass concentration of the concentrated sulfuric acid is 95-98%.

5. The method for preparing an energy-saving refractory material for RH refining furnace according to claim 3, characterized in that: The working gas for the radio frequency plasma treatment is argon and oxygen in a volume ratio of 4 to 5:1, the gas pressure is 5 to 10 Pa, and the power is set to 100 to 200W.

6. The method for preparing an energy-saving refractory material for a RH refining furnace according to claim 4, characterized in that: The copper plating solution contains: 15-26 g / L of disodium ethylenediaminetetraacetate, 10-22 g / L of copper sulfate, 10-18 g / L of nitrilotriacetic acid, 10-15 ml / L of formaldehyde, 8-12 g / L of potassium hydroxide, and the solvent is water.

7. The method for preparing an energy-saving refractory material for RH refining furnace according to claim 1, characterized in that: The ball milling mixing time in S2 is 18 to 30 hours, the rotation speed is 120 to 180 rpm, and the binder is phenolic resin.

8. The method for preparing an energy-saving refractory material for RH refining furnace according to claim 1, characterized in that: The vibration frequency in S3 is 30-55 Hz, the molding pressure is 130-185 MPa, and the holding time is 1-2 h.

Citation Information

Cited By

  • Inorganic castable and production process

    CN120943618A